A self‐enforcing CD44s/ZEB1 feedback loop maintains EMT and stemness properties in cancer cells. Issue 11 (30th June 2015) - Preca, Bogdan‐Tiberius; Bajdak, Karolina; Mock, Kerstin; Sundararajan, Vignesh; Pfannstiel, Jessica; Maurer, Jochen; Wellner, Ulrich; Hopt, Ulrich T.; Brummer, Tilman; Brabletz, Simone; Brabletz, Thomas; Stemmler, Marc P.
Abstract : Invasion and metastasis of carcinomas are often activated by induction of aberrant epithelial–mesenchymal transition (EMT). This is mainly driven by the transcription factor ZEB1, promoting tumor‐initiating capacity correlated with increased expression of the putative stem cell marker CD44. However, the direct link between ZEB1, CD44 and tumourigenesis is still enigmatic. Remarkably, EMT‐induced repression of ESRP1 controls alternative splicing of CD44, causing a shift in the expression from the variant CD44v to the standard CD44s isoform. We analyzed whether CD44 and ZEB1 regulate each other and show that ZEB1 controls CD44s splicing by repression of ESRP1 in breast and pancreatic cancer. Intriguingly, CD44s itself activates the expression of ZEB1, resulting in a self‐sustaining ZEB1 and CD44s expression. Activation of this novel CD44s‐ZEB1 regulatory loop has functional impact on tumor cells, as evident by increased tumor‐sphere initiation capacity, drug‐resistance and tumor recurrence. In summary, we identified a self‐enforcing feedback loop that employs CD44s to activate ZEB1 expression. This renders tumor cell stemness independent of external stimuli, as ZEB1 downregulates ESRP1, further promoting CD44s isoform synthesis. Abstract : What's new? The acquisition of an aggressive phenotype in tumors is associated with the epithelial–mesenchymal transition (EMT) program and expression of EMT activators, particularly ZEB1. ZEB1 expression is correlated with expression of CD44, a cancer stem cell marker. The authors of this study have uncovered a self‐sustaining regulatory feedback loop between ZEB1 and CD44. Initial EMT‐inducing activity promotes signaling via the mesenchymal CD44 isoform (CD44s), which regulates ZEB1 expression. ZEB1, in turn, represses the epithelial splicing regulator ESRP1, thereby enforcing CD44s splicing and allowing cancer cells to become independent of external EMT stimuli to provide stemness and metastasis.